Implementasi Digital Accounting Pada Era Digitalisasi Untuk Meningkatkan Performa Umkm Dikelurahan Desa Tambak Sawah Waru Sidoarjo - Fitriandinni, Reza Mutiara Nur; Riyadi, Slamet (Cattleya Darmaya Fortuna, 2025)
In accounting, digital accounting is the use of digital technology to create financial reports that are more efficient, accurate, and transparent. This transformation greatly affects UMKM, especially in the era of digitalization, when business competition is becoming increasingly fierce and the demand for good financial management is rising. This research aims to use digital accounting to improve the performance of UMKM in Tambak Sawah Village, Waru, Sidoarjo. This village was chosen because of the diverse conditions of its UMKM. Most people still use manual bookkeeping, although some have switched to digital bookkeeping. The purpose of this research is to determine the extent to which UMKM in Tambak Sawah Village are familiar with and use digital accounting, as well as to identify the advantages and disadvantages of digital accounting. In addition to documentation from ten micro, small, and medium enterprises (UMKM) that were the subjects of the study, research data were collected through direct observation and in-depth interviews using a descriptive qualitative approach. The research results show that some micro, small, and medium enterprises (UMKM) have not yet implemented a digital accounting system because they lack the necessary information. However, some UMKM have successfully implemented this system. The implementation of a digital accounting system may improve the performance of UMKM in Tambak Sawah village, Waru, Sidoarjo Regency. By using this digital accounting system, the recording and reporting of financial information become easier, and data can be protected from loss.